2019
DOI: 10.1029/2019gc008393
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transport and Structural Properties of Binary Liquid Iron Alloys at High Pressure

Abstract: We determine mass transport and structural properties of binary liquid iron alloys over a wide density (5.055–11.735 g·cm−3) and temperature range (2,500–6,500 K) using first‐principles molecular dynamics. Compositions consist of 96 at% Fe and 4 at% ϕ, where ϕ = H, C, N, O, Mg, Si, S, or Ni. Self‐diffusion coefficients (D) of Fe and ϕ range from 3.5·10−9 to 1.9·10−7 m2·s−1. Results show a relation between mean atomic radius and diffusivity ratio for the alloying element and iron: Si and Ni are “iron‐like” with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 64 publications
3
24
0
Order By: Relevance
“…This is due to the fact that the silicate melt structure undergoes radical atomic arrangement from four‐ to six‐fold Si‐O coordination (SI, Figure S6a): While the nearest neighbor O‐H distance represented by the principal peak position in g HO ( r ) (SI, Figure S6b) remains at virtually the same distance, the second neighbor O‐H distances are shifted to considerably lower r with increasing P , reflected in the decrease of Vtrue¯SH with P . By contrast, the average interatomic distance between Fe and H in the metallic melts remains constant over the same P ‐range (SI, Figure S6d), similar to the results reported in a previous DFT‐MD study (Posner & Steinle‐Neumann, 2019). At higher P , differences are Δ r V/ Vtrue¯SH = −16% (40 GPa, 4,000 K) and −12% (130 GPa, 4,000 K), and they contribute more significantly to G by a P Δ r V energy component due to large P : The P Δ r V term increases from −0.13 eV at 20 GPa and 2,500 K, to −0.54 eV at 40 GPa and 4,000 K, and −0.88 eV at 130 GPa and 4,000 K (Figures 2d – 2f; SI, Table S2).…”
Section: Resultssupporting
confidence: 87%
“…This is due to the fact that the silicate melt structure undergoes radical atomic arrangement from four‐ to six‐fold Si‐O coordination (SI, Figure S6a): While the nearest neighbor O‐H distance represented by the principal peak position in g HO ( r ) (SI, Figure S6b) remains at virtually the same distance, the second neighbor O‐H distances are shifted to considerably lower r with increasing P , reflected in the decrease of Vtrue¯SH with P . By contrast, the average interatomic distance between Fe and H in the metallic melts remains constant over the same P ‐range (SI, Figure S6d), similar to the results reported in a previous DFT‐MD study (Posner & Steinle‐Neumann, 2019). At higher P , differences are Δ r V/ Vtrue¯SH = −16% (40 GPa, 4,000 K) and −12% (130 GPa, 4,000 K), and they contribute more significantly to G by a P Δ r V energy component due to large P : The P Δ r V term increases from −0.13 eV at 20 GPa and 2,500 K, to −0.54 eV at 40 GPa and 4,000 K, and −0.88 eV at 130 GPa and 4,000 K (Figures 2d – 2f; SI, Table S2).…”
Section: Resultssupporting
confidence: 87%
“…In particular, in the latter, empirical pressure corrections of 10 GPa and 8 GPa were adopted at the CMB and ICB respectively, though the optimized OC compositions are essentially sensitive to these corrections. Meanwhile, some studies have been performed throughout the whole OC P, T conditions for pure Fe [7,26], Fe-S [27], and Fe-H [28]. However, different formulations were employed to model their thermal equations of state, making a quantitative comparison of the reported thermoelasticity not easy.…”
Section: Introductionmentioning
confidence: 99%
“…These features align with the results of earlier studies. [ 17,21,22,23 ] In addition, g OO ( r ) and g SiSi ( r ) do not depend on the LE concentration. For g FeFe ( r ), there were no differences in all systems.…”
Section: Resultsmentioning
confidence: 99%
“…[ 19 ] Theoretically, the structures of liquid FeH, FeC, FeN, FeO, FeMg, FeSi, and FeS under high pressure were investigated by ab initio molecular dynamics simulations. [ 20–23 ] Alfè and Gillan investigated the structure of liquid FeS at 6000 K and 330 GPa and suggested that there was no tendency for S atoms to form chains, despite the fact that pure sulfur is known to form chains in the liquid phase. [ 20 ] The structural properties of liquid FeO under high pressure were also investigated by ab initio MD simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation